Usability and acceptability of self-testing for hepatitis C virus infection among the general population in the Nile Delta region of Egypt - Elena Ivanova Reipold; Ahmed Farahat; Amira Elbeeh; Reham Soliman; Elkin Bermudez Aza; Muhammad S. Jamil; Cheryl Case Johnson; Gamal Shiha; Philippa Easterbrook (BMC, 2021)
Abstract Background Self-testing for hepatitis C virus antibodies (HCVST) may be an additional strategy to expand access to hepatitis C virus (HCV) testing and support elimination efforts. We conducted a study to assess the usability and acceptability of HCVST among the general population in a semi-rural, high-HCV prevalence region in Egypt. Methods An observational study was conducted in two hospitals in the Nile Delta region. A trained provider gave an in-person demonstration on how to use the oral fluid HCVST followed by observation of the participant performing the test. Usability was assessed by observing errors made and difficulties faced by participants. Acceptability of HCV self-testing was assessed using an interviewer-administered semi-structured questionnaire. Results Of 116 participants enrolled, 17 (14.6%) had received no formal education. The majority (72%) of participants completed all testing steps without any assistance and interpreted the test results correctly. Agreement between participant-reported HCVST results and interpretation by a trained user was 86%, with a Cohen's kappa of 0.6. Agreement between participant-reported HCVST results and provider-administered oral fluid HCV rapid test results was 97.2%, with a Cohen's kappa of 0.75. The majority of participants rated the HCVST process as easy (53%) or very easy (44%), and 96% indicated they would be willing to use HCVST again and recommend it to their family and friends. Conclusion Our study demonstrates the high usability and acceptability of oral fluid HCVST in a general population. Further studies are needed to establish the optimal positioning of self-testing alongside facility-based testing to expand access to HCV diagnosis in both general and high-risk populations.